The Impact of Advertising Content on Purchase Intention: The Mediating Role of Brand Awareness and Brand Image with Generation Z Moderation - Yohanes Ferry Cahaya; Alloysius Pamurda Dhika Mahendra; Herni Pujiati; Ilham Nawang Armanda (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2026)
This study examines the influence of advertising content on purchase intention among 500 consumers in Jakarta, Indonesia, focusing on Generation Z as a moderating factor. Employing Partial Least Squares Structural Equation Modeling (PLS-SEM), we investigate the mediating roles of brand awareness and brand image in the advertising- purchase intention relationship. Results demonstrate that advertising content significantly affects purchase intention both directly and indirectly through brand awareness and brand image. Generation Z membership significantly moderates these relationships, amplifying the effects of advertising content on brand outcomes. These findings contribute to advertising effectiveness theory and provide actionable insights for marketers targeting digitally- native consumers in emerging markets. The comprehensive model explains substantial variance in purchase intention, offering practical implications for developing generation-specific marketing strategies.